Health agents in the context of medical plurality of Haquira. Apurimac, Peru - Astete Checaña, Marco Antonio (2018)
Introduction. Our research was objetive to describe the presence and social role of health agents in the dynamic context of district Haquira, Apurímac region, Peru. Methods. Qualitative study in which the ethnographic technique was used. Fieldwork was used in which in-depth interviews, conversations and participant observation were used. Results. A context of plurality of health systems is evidenced by the diversity of agents and the use of therapeutic repertoires. The holistic conception of health is based on the search for balance. The population is characterized by self-care and this allows the formation of “curious” people who excel in health knowledge. Local agents start as curious and their options are to become amateurs, specialists or professionals. There is a proliferation of amateurs, there is a preference for the training of professionals and there is a low rate for the training of traditional specialists. With the accelerated changes in the context and the holistic conception of health, the arrival of new foreign agents is welcomed. Conclusions. There is a great diversity of health agents. Local agents are decreasing, due to the advancement of modernity, the subordination of these to the official system, the proliferation of the medical offer, greater access to information for the population. There is no health rectorial work, there is no recognition of traditional agents, there is no control to those who offer services or medicines. It is necessary to make a mapping of the health agents as a first step to establish works based on intercultural dialogue.